Synthesis and biological evaluation of benzimidazole pendant cyanopyrimidine derivatives as anticancer agents. (27th July 2020) - Haoran, Wang; Akhtar, Wasim; Nainwal, Lalit Mohan; Kaushik, Sumit Kumar; Akhter, Mymoona; Shaquiquzzaman, Mohammad; Alam, Mohammad Mumtaz
Abstract: Thirteen new benzimidazole pendant cyanopyrimidine derivatives were synthesized. The compounds were synthesized through multistep reaction protocol. The structures of synthesized derivatives were studied by EI‐MS, 1 H NMR, FT‐IR and elemental analysis. All the compounds were studied for their anticancer activity at National Cancer Institute. Except compound 7j, all the compounds unveiled cytotoxicity against cancer cells. The most active compound 7a had shown highest value of growth inhibition of 88.44% and 84.19% against HOP‐92 and T‐47D cancer cell lines. Abstract :